High-weather-resistance ultraviolet and infrared barrier EVA optical adhesive film and preparation method thereof

The preparation of high weathering ultraviolet infrared barrier EVA optical adhesive films through the raw materials with specific ratios has solved the problems of poor weathering resistance and affected photocuring performance of the existing EVA optical adhesive films, achieving high weathering resistance and thermal insulation durability, and is suitable for outdoor electronic display screens.

CN119592249APending Publication Date: 2025-03-11ZHONGCHUANG KEDA (FOSHAN) TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411866908.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing EVA optical adhesive film has poor weather resistance, and the properties of the adhesive film after photocuring are easily affected by ultraviolet absorbers, making it difficult to use in outdoor environments for a long time.

Method used

High weather-resistant ultraviolet infrared barrier EVA optical adhesive film is prepared using raw materials with specific ratios, including ethylene-vinyl acetate copolymer, acrylate monomer, photoinitiator, ultraviolet absorber, coupling agent, light stabilizer and heat insulation slurry. It absorbs the entire band of ultraviolet rays through UV curing and uses the synergistic effect of the two to prevent aging.

Benefits of technology

It realizes high weather resistance and thermal insulation durability of EVA optical adhesive film, and is suitable for outdoor electronic displays, which can block ultraviolet and infrared light at the same time, maintaining excellent thermal insulation performance and appearance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005194631710000021
    Figure BDA0005194631710000021
  • Figure BDA0005194631710000131
    Figure BDA0005194631710000131
  • Figure BDA0005194631710000141
    Figure BDA0005194631710000141
Patent Text Reader

Abstract

The invention discloses a high-weather-resistance ultraviolet infrared barrier EVA optical adhesive film and a preparation method thereof, and the optical adhesive film is prepared from the following raw materials by weight: 100 parts of an ethylene-vinyl acetate copolymer; 1-20 parts of an acrylate monomer; 2-5 parts of a photoinitiator; 0.1-2 parts of an ultraviolet light absorber; 0.1 to 10 parts of a coupling agent; 0.1-2 parts of a light stabilizer; and 10-40 parts of heat insulation slurry. The ultraviolet light absorber can absorb ultraviolet light in a certain interval, the photoinitiator can absorb ultraviolet light in another interval to initiate a curing reaction, through the synergistic effect of the ultraviolet light absorber and the photoinitiator, ultraviolet light in a full wave band can be absorbed, and meanwhile ultraviolet absorption of the photoinitiator is not affected; according to the EVA optical adhesive film, the curing reaction is ensured, the aging problem caused by long-term irradiation of ultraviolet rays can be resisted, inward shrinkage of the EVA optical adhesive film can be prevented by adopting the heat insulation slurry with specific components, so that the EVA optical adhesive film is excellent and lasting in heat insulation performance and good in appearance, and the EVA optical adhesive film can block ultraviolet light and infrared light at the same time, and has a good application prospect. The weather resistance and the heat insulation durability are high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of optical adhesive films, and relates to an EVA optical adhesive film and a preparation method thereof, and specifically to a highly weather-resistant ultraviolet and infrared blocking EVA optical adhesive film and a preparation method thereof. Background Art

[0002] With the rapid development of electronic technology, electronic devices such as mobile phones, various computers, televisions, and advertising display screens can be seen everywhere. Display devices such as touch screens and LCD screens have developed rapidly. During the production and processing of touch screens and other display devices, optical adhesive films are required to bond components. Optical adhesive films have the advantages of being colorless and transparent, with a light transmittance of more than 90%, and high bonding strength. Traditional optical adhesive films include OCA (Optically Clear Adhesive) optical adhesive and LOCA (Liquid Optical Clear Adhesive) optical adhesive. These two optical adhesives have good effects, but there are technical defects in both process and performance. Among them, OCA optical adhesive has the problems of difficulty in bonding and easy generation of bubbles; LOCA optical adhesive has the problems of easy flow of glue, difficulty in removing bubbles, difficulty in rework, and low production efficiency, which is not conducive to the bonding of large-size touch screens and LCD screens.

[0003] In order to solve the above technical problems, in recent years, EVA (ethylene-vinyl acetate copolymer) optical adhesive film has been favored because of its advantages such as easy processing, easy bubble removal, easy rework, high product yield, and excellent mechanical properties, and has gradually replaced the traditional OCA optical adhesive and LOCA optical adhesive. However, a single EVA optical adhesive film has problems such as easy yellowing and poor weather resistance, and cannot be used in outdoor large screens and electronic display screens that need to be installed in outdoor environments. In order to realize the application of outdoor environment display screens, Chinese patent CN105086859A discloses an EVA composite optical film doped with metal elements using vanadium dioxide; Chinese patent CN104130725A discloses an EVA composite optical film added with tungsten-doped cerium antimony tin dioxide. The technologies disclosed in the above patents all compound nanomaterials with EVA to obtain EVA composite optical films, and utilize the thermal insulation properties of nanomaterials to enable the EVA composite optical film to meet the application requirements of outdoor large screens and achieve the purpose of energy saving. However, the above-mentioned EVA composite film still has the problem of poor weather resistance. Long-term use in sunlight will cause the EVA film to shrink, which affects both its thermal insulation performance and its appearance, and has certain limitations in use.

[0004] In addition, EVA optical films often require UV curing during the preparation process. During the UV curing process, the photoinitiator needs to absorb ultraviolet light and decompose into free radicals or cations to initiate polymerization reactions. The demand for EVA optical films to resist environmental aging requires the addition of ultraviolet absorbers during the preparation process of the EVA optical film. The ultraviolet absorber can absorb some wavelengths of ultraviolet rays, but it will affect the function of the photoinitiator, ultimately affecting the curing process and the performance of the cured EVA optical adhesive film.

[0005] In view of this, it is necessary to further improve the EVA optical adhesive film in the prior art. Summary of the invention

[0006] To this end, the technical problem to be solved by the present invention is that the EVA optical adhesive film in the prior art has poor weather resistance and the performance of the film after photocuring is easily affected by ultraviolet absorbers, thereby proposing a highly weather-resistant ultraviolet and infrared blocking EVA optical adhesive film and a preparation method thereof.

[0007] In order to solve the above technical problems, the technical solution of the present invention is:

[0008] The first aspect of the present invention provides a highly weather-resistant ultraviolet and infrared blocking EVA optical adhesive film, which is prepared from the following raw materials in parts by weight:

[0009]

[0010] Preferably, the ethylene-vinyl acetate copolymer has a melt index of 5-43 g / 10 min and a VA content of 28-33%.

[0011] Preferably, the acrylate monomer is at least one of trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, trimethylolpropane diacrylate, and di-trimethylolpropane tetraacrylate (ditrimethylolpropane tetraacrylate).

[0012] Preferably, the photoinitiator includes at least one of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide or liquid 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and at least one of GC-1005A and GC-1003.

[0013] Preferably, the ultraviolet absorber is one of ultraviolet absorber 5400 and ultraviolet absorber UV-971.

[0014] Preferably, the coupling agent is at least one of vinyl triethoxysilane, γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane, and γ-(methacryloyloxy)propyl trimethoxysilane.

[0015] Preferably, the antioxidant is antioxidant 1076; and the light stabilizer is light stabilizer 770.

[0016] Preferably, the thermal insulation slurry is an oily dispersion of GTO wrapped in silica.

[0017] The second aspect of the present invention provides a method for preparing the highly weather-resistant ultraviolet and infrared blocking EVA optical adhesive film, which comprises the following steps:

[0018] S1. Prepare thermal insulation slurry, disperse GTO powder in water to obtain a dispersion; add sodium silicate aqueous solution to the dispersion, stir to react, obtain a reaction solution, adjust the pH of the reaction solution to 8-10, continue to stir to react, filter to obtain a reactant, dry the reactant and then sinter to obtain a silica-coated GTO powder, mix the silica-coated GTO powder with a dispersant and a solvent to obtain the thermal insulation slurry;

[0019] S2. Prepare an EVA optical adhesive film, mix the ethylene-vinyl acetate copolymer, acrylate monomer, photoinitiator, ultraviolet absorber, coupling agent, light stabilizer, and thermal insulation slurry according to a ratio, perform pre-pressing treatment, and after the pre-pressing treatment, irradiate under a high-pressure mercury lamp to obtain the EVA optical adhesive film.

[0020] Preferably, in step S1, the concentration of the dispersion is 10-30%, the concentration of the sodium silicate aqueous solution is 1-30%, and the stirring reaction time is 1-3h; in the sintering process, the sintering temperature is 600-1000°C, and the sintering time is 4-6h; in step S2, the pre-pressing temperature is 60-80°C, the pre-pressing time is 4-6min, the irradiation time of the high-pressure mercury lamp is 2-5min, and the irradiation intensity is 3000-10000mj / cm 2 ; In the step S1, the dispersant is one of BYK-ATU, DP-810, EFKA-5220, BYK-110, S-32500, BYK-161, S-2000, EFKA-4010; the solvent is one or more of cyclohexane, toluene, xylene, ethylene glycol butyl ether acetate, and propylene glycol methyl ether acetate.

[0021] The above technical solution of the present invention has the following advantages compared with the prior art:

[0022] The highly weather-resistant ultraviolet and infrared blocking EVA optical adhesive film provided by the present invention is prepared from the following raw materials, measured in parts by weight: 100 parts of ethylene-vinyl acetate copolymer; 1-20 parts of acrylate monomer; 2-5 parts of photoinitiator; 0.1-2 parts of ultraviolet absorber; 0.1-10 parts of coupling agent; 0.1-2 parts of light stabilizer; and 10-40 parts of thermal insulation slurry. Among them, the ultraviolet absorber can absorb ultraviolet rays in a certain range, and the photoinitiator can absorb ultraviolet rays in another range to initiate a curing reaction. Therefore, through the synergistic effect of the two, it can absorb ultraviolet rays of the entire band without affecting the ultraviolet absorption of the photoinitiator, thereby ensuring the curing reaction while resisting aging problems caused by long-term exposure to ultraviolet rays. By adopting a thermal insulation slurry with specific ingredients, the EVA optical adhesive film can also be prevented from shrinking, making the EVA optical adhesive film have excellent and durable thermal insulation performance, and also ensuring the appearance of the optical adhesive film. The EVA optical adhesive film can block ultraviolet light and infrared light at the same time, has high weather resistance and thermal insulation durability, and is suitable for electronic display screens, especially electronic display screens used in outdoor environments. DETAILED DESCRIPTION

[0023] Example 1

[0024] The present embodiment provides a highly weather-resistant ultraviolet and infrared blocking EVA optical adhesive film, which is prepared from the following raw materials, in parts by weight: 100 parts of ethylene-vinyl acetate copolymer (EVA) with a VA content of 28% and a melt index of 5g / 10min (i.e., the total weight of the EVA base material is 100 parts), 1 part of trimethylolpropane diacrylate, 3 parts of photoinitiator 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO), 2 parts of photoinitiator GC-1005A, 0.1 parts of ultraviolet absorber 5400, 10 parts of coupling agent γ-aminopropyltriethoxysilane, 0.1 parts of antioxidant 1076, 2 parts of light stabilizer 770, and 40 parts of thermal insulation slurry, wherein the thermal insulation slurry is an oily dispersion of GTO wrapped in silica.

[0025] In the highly weather-resistant ultraviolet and infrared blocking EVA optical adhesive film provided in this embodiment, the ultraviolet absorber can absorb ultraviolet rays in a certain range (the absorption peak of ultraviolet absorber 5400 is 275nm-320nm, and the absorption peak of ultraviolet absorber UV971 is 275-300nm), and the photoinitiator can absorb ultraviolet rays in another range (the absorption peak of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide photoinitiator is 350nm-400nm, the absorption peak of liquid 2,4,6-trimethylbenzoyl-diphenylphosphine oxide photoinitiator is 270-370nm, and the absorption peak range of photoinitiators GC1005A and GC-1003 is approximately 200-300nm) to initiate the curing reaction, so that through the synergistic effect of the two, the full-band ultraviolet rays can be absorbed, and at the same time It does not affect the ultraviolet absorption of the photoinitiator, ensures the curing reaction and can resist the aging problem caused by long-term ultraviolet radiation. By adopting a thermal insulation slurry with a specific composition, the EVA optical adhesive film can also be prevented from shrinking. Specifically, the thermal insulation slurry adopts an oily dispersion of GTO wrapped with silica, which has the function of isolating water vapor, and works together with the ultraviolet absorber to prevent the problem of shrinkage of the EVA optical adhesive film, so that the EVA optical adhesive film has excellent and durable thermal insulation performance and ensures the appearance of the optical adhesive film. At the same time, the GTO in the thermal insulation slurry also has the function of blocking infrared rays, so that the EVA optical adhesive film can block ultraviolet light and infrared light at the same time, has a heat insulation effect, and has high weather resistance and heat insulation durability, and is suitable for electronic display screens, especially electronic display screens used in outdoor environments.

[0026] The highly weather-resistant ultraviolet and infrared blocking EVA optical adhesive film provided in this embodiment is prepared by the following steps:

[0027] S1. Prepare thermal insulation slurry, disperse GTO powder in water to obtain a dispersion with a concentration of 10%; add 100 ml of sodium silicate aqueous solution with a concentration of 1% to the dispersion, stir and react for 1 hour to obtain a reaction solution, adjust the pH of the reaction solution to 8, continue to stir and react for 1 hour, filter to obtain a precipitated reactant, dry the precipitated reactant, and sinter at 600°C for 4 hours to obtain silica-coated GTO powder, and mix the silica-coated GTO powder with dispersant BYK-ATU and cyclohexane to obtain thermal insulation slurry. By wrapping GTO with silica, moisture in the air can be isolated, the EVA film can be prevented from shrinking, and the durability of the thermal insulation effect is improved.

[0028] S2. Prepare EVA optical adhesive film. According to the above ratio, mix the raw materials evenly and extrude them. Then, pre-press them with a vacuum press at 60°C for 4 minutes and irradiate them under a high-pressure mercury lamp with a light intensity of 3KW for 2 minutes. The irradiation intensity is 3000mj / cm 2 After the irradiation, the EVA film is obtained.

[0029] Example 2

[0030] The present embodiment provides a highly weather-resistant ultraviolet and infrared blocking EVA optical adhesive film, which is prepared from the following raw materials, in parts by weight: 100 parts of ethylene-vinyl acetate copolymer (EVA) with a VA content of 33% and a melt index of 43 g / 10 min, 20 parts of ditrimethylolpropane tetraacrylate, 1 part of liquid 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO-L) photoinitiator, 1 part of photoinitiator GC-1003, 2 parts of ultraviolet absorber UV-971, 0.1 parts of coupling agent γ-(methacryloyloxy)propyltrimethoxysilane, 5 parts of antioxidant 1076, 0.1 parts of light stabilizer 770, and 10 parts of thermal insulation slurry, wherein the thermal insulation slurry is an oily dispersion of GTO wrapped in silica.

[0031] The highly weather-resistant ultraviolet and infrared blocking EVA optical adhesive film provided in this embodiment is prepared by the following steps:

[0032] S1. Prepare thermal insulation slurry, disperse GTO powder in water to obtain a dispersion with a concentration of 30%; add 600 ml of a 30% sodium silicate aqueous solution to the dispersion, stir and react for 3 hours to obtain a reaction solution, adjust the pH of the reaction solution to 10, continue to stir and react for 3 hours, filter to obtain a precipitated reactant, dry the precipitated reactant, and sinter at 1000° C. for 6 hours to obtain silica-coated GTO powder, and mix the silica-coated GTO powder with a dispersant EFKA-5220 and toluene to obtain a thermal insulation slurry.

[0033] S2. Prepare EVA optical adhesive film. According to the above ratio, mix the raw materials evenly and extrude them. Then, pre-press them with a vacuum press at 80°C for 6 minutes and irradiate them under a high-pressure mercury lamp with a light intensity of 3KW for 5 minutes. The irradiation intensity is 10000mj / cm 2 After the irradiation, the EVA film is obtained.

[0034] Example 3

[0035] The present embodiment provides a highly weather-resistant ultraviolet and infrared blocking EVA optical adhesive film, which is prepared from the following raw materials, in parts by weight: 100 parts of ethylene-vinyl acetate copolymer (EVA) with a VA content of 30% and a melt index of 24 g / 10 min, 5 parts of trimethylolpropane trimethacrylate, 5 parts of trimethylolpropane diacrylate, 1.5 parts of photoinitiator 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 1.5 parts of photoinitiator GC1005A, 11 parts of ultraviolet absorber UV-97, 2 parts of coupling agent γ-aminopropyltriethoxysilane, 3 parts of coupling agent γ-(methacryloyloxy)propyltrimethoxysilane, 2.5 parts of antioxidant 1076, 1 part of light stabilizer 770, and 25 parts of thermal insulation slurry, wherein the thermal insulation slurry is an oily dispersion of GTO wrapped in silica. In this embodiment, by using 2,4,6-trimethylbenzoyl-diphenylphosphine oxide photoinitiator and GC1005A photoinitiator in a compound form, the compound photoinitiator has absorption peaks at 200nm-300nm and 350nm-400nm respectively, and the ultraviolet absorber can absorb ultraviolet rays of about 270nm-300nm. Such a combination of ultraviolet absorber and photoinitiator can absorb ultraviolet rays of the entire band and does not affect photocuring while absorbing ultraviolet rays.

[0036] The highly weather-resistant ultraviolet and infrared blocking EVA optical adhesive film provided in this embodiment is prepared by the following steps:

[0037] S1. Prepare thermal insulation slurry, disperse GTO powder in water to obtain a dispersion with a concentration of 20%; add 400 ml of a sodium silicate aqueous solution with a concentration of 15% to the dispersion, stir and react for 2 hours to obtain a reaction solution, adjust the pH of the reaction solution to 9, continue to stir and react for 2 hours, filter to obtain a precipitated reactant, dry the precipitated reactant, and sinter at 800°C for 5 hours to obtain silica-coated GTO powder, mix the silica-coated GTO powder with a dispersant BYK-110 and ethylene glycol butyl ether acetate to obtain a thermal insulation slurry.

[0038] S2. Prepare EVA optical adhesive film. According to the above ratio, mix the raw materials evenly and extrude them. Then, pre-press them with a vacuum press at 70°C for 5 minutes, and irradiate them under a high-pressure mercury lamp with a light intensity of 3KW for 3 minutes. The irradiation intensity is 6000mj / cm 2 After the irradiation, the EVA film is obtained.

[0039] Example 4

[0040] The present embodiment provides a highly weather-resistant ultraviolet and infrared blocking EVA optical adhesive film, which is prepared by the following steps: by weight, 100 parts of ethylene-vinyl acetate copolymer with a VA content of 28% and a melt index of 15, 10 parts of trimethylolpropane triacrylate acrylate monomer, 0.5 parts of coupling agent vinyl triethoxysilane, 1 part of 1076 antioxidant, 0.5 parts of 770 light stabilizer, 30 parts of thermal insulation slurry, 1.5 parts of photoinitiator TPO, 0.8 parts of GC1005A, and 1 part of 5400 ultraviolet absorber are mixed uniformly to obtain a mixture, wherein the thermal insulation slurry is prepared by the method provided in Example 3. The mixture is mixed uniformly and extruded by an extruder, the extrusion temperature is 70°C, and after extrusion, it is cooled, embossed, pulled, and rolled to obtain an uncured EVA optical adhesive film. In this embodiment, the thickness of the uncured EVA optical adhesive film is 0.4 mm.

[0041] The uncured EVA optical adhesive film obtained in the above step was placed in a vacuum press, pre-pressed at 80°C for 4 minutes, and then irradiated under a high-pressure mercury lamp with a light intensity of 3KW for 3 minutes, with an irradiation intensity of 5000mj / cm 2 After irradiation, the highly weather-resistant UV-IR blocking EVA optical film is obtained.

[0042] Example 5

[0043] The present embodiment provides a highly weather-resistant ultraviolet and infrared blocking EVA optical adhesive film, which is prepared by the following steps: by weight, 100 parts of ethylene-vinyl acetate copolymer with a VA content of 28% and a melt index of 20, 10 parts of trimethylolpropane trimethacrylate, 0.6 parts of coupling agent γ-glycidyloxypropyl trimethoxysilane, 1 part of 1076 antioxidant, 0.6 parts of 770 light stabilizer, 30 parts of thermal insulation slurry, 1 part of photoinitiator TPO, 0.5 parts of photoinitiator TPO-L, 0.8 parts of GC1005A, and 1.5 parts of 971 ultraviolet absorber are mixed uniformly to obtain a mixture, wherein the thermal insulation slurry is prepared by the method provided in Example 3. The mixture is mixed uniformly and extruded by an extruder, the extrusion temperature is 70°C, and after extrusion, it is cooled, embossed, pulled, and rolled to obtain an uncured EVA optical adhesive film. In this embodiment, the thickness of the uncured EVA optical adhesive film is 0.4 mm.

[0044] The uncured EVA optical adhesive film obtained in the above step was placed in a vacuum press, pre-pressed at 70°C for 4 min, and then irradiated under a high-pressure mercury lamp with a light intensity of 3KW for 3 min. The irradiation intensity was 6000mj / cm 2 After irradiation, the highly weather-resistant UV-IR blocking EVA optical film is obtained.

[0045] Comparative Example 1

[0046] This comparative example provides an EVA optical adhesive film, which is prepared by the following steps: by weight, 100 parts of ethylene-vinyl acetate copolymer with a VA content of 28% and a melt index of 15, 10 parts of trimethylolpropane triacrylate acrylate monomer, 0.5 parts of coupling agent vinyl triethoxysilane, 1 part of 1076 antioxidant, 0.5 parts of 770 light stabilizer, 30 parts of thermal insulation slurry, 1.5 parts of photoinitiator TPO, and 1 part of 5400 ultraviolet absorber are mixed uniformly to obtain a mixture, wherein the thermal insulation slurry is prepared by the method provided in Example 3. The mixture is mixed uniformly and extruded by an extruder, the extrusion temperature is 70°C, and after extrusion, it is cooled, embossed, pulled, and rolled to obtain an uncured EVA optical adhesive film. In this embodiment, the thickness of the uncured EVA optical adhesive film is 0.4 mm.

[0047] The uncured EVA optical adhesive film obtained in the above step was placed in a vacuum press, pre-pressed at 80°C for 4 minutes, and then irradiated under a high-pressure mercury lamp with a light intensity of 3KW for 3 minutes, with an irradiation intensity of 5000mj / cm 2 After the irradiation, the EVA optical adhesive film is obtained. Compared with Example 4, the photoinitiator GC1005A is not added in this comparative example.

[0048] Comparative Example 2

[0049] This comparative example provides an EVA optical adhesive film, which is prepared by the following steps: by weight, 100 parts of ethylene-vinyl acetate copolymer with a VA content of 28% and a melt index of 15, 10 parts of trimethylolpropane triacrylate acrylate monomer, 0.5 parts of coupling agent vinyl triethoxysilane, 1 part of 1076 antioxidant, 0.5 parts of 770 light stabilizer, 30 parts of thermal insulation slurry, 0.8 parts of photoinitiator GC1005A, and 1 part of 5400 ultraviolet absorber are mixed uniformly to obtain a mixture, wherein the thermal insulation slurry is prepared by the method provided in Example 3. The mixture is mixed uniformly and extruded by an extruder, the extrusion temperature is 70°C, and after extrusion, it is cooled, embossed, pulled, and rolled to obtain an uncured EVA optical adhesive film. In this embodiment, the thickness of the uncured EVA optical adhesive film is 0.4 mm.

[0050] The uncured EVA optical adhesive film obtained in the above step was placed in a vacuum press, pre-pressed at 80°C for 4 minutes, and then irradiated under a high-pressure mercury lamp with a light intensity of 3KW for 3 minutes, with an irradiation intensity of 5000mj / cm 2 After the irradiation, the EVA optical adhesive film is obtained. Compared with Example 4, the photoinitiator TPO is not added in this comparative example.

[0051] Comparative Example 3

[0052] This comparative example provides an EVA optical adhesive film, which is prepared by the following steps: by weight, 100 parts of ethylene-vinyl acetate copolymer with a VA content of 28% and a melt index of 20, 10 parts of trimethylolpropane trimethacrylate, 0.6 parts of coupling agent γ-glycidyloxypropyl trimethoxysilane, 1 part of 1076 antioxidant, 06 parts of 770 light stabilizer, 30 parts of thermal insulation slurry, 1 part of photoinitiator TPO, 0.5 parts of photoinitiator TPO-L, and 1.5 parts of 971 ultraviolet absorber are mixed uniformly to obtain a mixture, wherein the thermal insulation slurry is prepared by the method provided in Example 3. The mixture is mixed uniformly and extruded by an extruder, the extrusion temperature is 70°C, and after extrusion, it is cooled, embossed, pulled, and rolled to obtain an uncured EVA optical adhesive film. In this embodiment, the thickness of the uncured EVA optical adhesive film is 0.4 mm.

[0053] The uncured EVA optical adhesive film obtained in the above step was placed in a vacuum press, pre-pressed at 70°C for 4 min, and then irradiated under a high-pressure mercury lamp with a light intensity of 3KW for 3 min. The irradiation intensity was 6000mj / cm 2 After the irradiation, the EVA optical adhesive film is obtained. Compared with Example 5, the photoinitiator GC1005A is not added in this comparative example.

[0054] Comparative Example 4

[0055] This comparative example provides an EVA optical adhesive film, which is prepared by the following steps: by weight, 100 parts of ethylene-vinyl acetate copolymer with a VA content of 28% and a melt index of 20, 10 parts of trimethylolpropane trimethacrylate, 0.6 parts of coupling agent γ-glycidyloxypropyl trimethoxysilane, 1 part of 1076 antioxidant, 0.6 parts of 770 light stabilizer, 30 parts of thermal insulation slurry, 0.8 parts of photoinitiator GC1005A, and 1.5 parts of 971 ultraviolet absorber are mixed uniformly to obtain a mixture, wherein the thermal insulation slurry is prepared by the method provided in Example 3. The mixture is mixed uniformly and extruded by an extruder, the extrusion temperature is 70°C, and after extrusion, it is cooled, embossed, pulled, and rolled to obtain an uncured EVA optical adhesive film. In this embodiment, the thickness of the uncured EVA optical adhesive film is 0.4 mm.

[0056] The uncured EVA optical adhesive film obtained in the above step was placed in a vacuum press, pre-pressed at 70°C for 4 min, and then irradiated under a high-pressure mercury lamp with a light intensity of 3KW for 3 min. The irradiation intensity was 6000mj / cm 2 After the irradiation, the EVA optical adhesive film is obtained. Compared with Example 5, the photoinitiator TPO and the photoinitiator TPO-L are not added in this comparative example.

[0057] Comparative Example 5

[0058] This comparative example provides an EVA optical adhesive film, which is prepared by the following steps: by weight, 100 parts of ethylene-vinyl acetate copolymer with a VA content of 28% and a melt index of 15, 10 parts of trimethylolpropane triacrylate acrylate monomer, 0.5 parts of coupling agent vinyl triethoxysilane, 1 part of 1076 antioxidant, 0.5 parts of 770 light stabilizer, 30 parts of thermal insulation slurry, 1.5 parts of photoinitiator 184, 0.8 parts of photoinitiator GC1005A, and 1 part of 5400 ultraviolet absorber are mixed uniformly to obtain a mixture, wherein the thermal insulation slurry is prepared by the method provided in Example 3. The mixture is mixed uniformly and extruded by an extruder, the extrusion temperature is 70°C, and after extrusion, it is cooled, embossed, pulled, and rolled to obtain an uncured EVA optical adhesive film. In this embodiment, the thickness of the uncured EVA optical adhesive film is 0.4 mm.

[0059] The uncured EVA optical adhesive film obtained in the above step was placed in a vacuum press, pre-pressed at 80°C for 4 minutes, and then irradiated under a high-pressure mercury lamp with a light intensity of 3KW for 3 minutes, with an irradiation intensity of 5000mj / cm 2 After the irradiation, the EVA optical adhesive film is obtained. Compared with Example 4, the photoinitiator TPO is replaced by the photoinitiator 184 in this comparative example, wherein the absorption peak of the photoinitiator 184 is 244nm-326nm.

[0060] Comparative Example 6

[0061] This comparative example provides an EVA optical adhesive film, which is prepared by the following steps: by weight, 100 parts of ethylene-vinyl acetate copolymer with a VA content of 28% and a melt index of 15, 10 parts of trimethylolpropane triacrylate acrylate monomer, 0.5 parts of coupling agent vinyl triethoxysilane, 1 part of 1076 antioxidant, 0.5 parts of 770 light stabilizer, 30 parts of thermal insulation slurry, 2 parts of photoinitiator 439, and 1 part of 5400 ultraviolet absorber are mixed uniformly to obtain a mixture, wherein the thermal insulation slurry is prepared by the method provided in Example 3. The mixture is mixed uniformly and extruded by an extruder, the extrusion temperature is 70°C, and after extrusion, it is cooled, embossed, pulled, and rolled to obtain an uncured EVA optical adhesive film. In this embodiment, the thickness of the uncured EVA optical adhesive film is 0.4 mm.

[0062] The uncured EVA optical adhesive film obtained in the above step was placed in a vacuum press, pre-pressed at 80°C for 4 minutes, and then irradiated under a high-pressure mercury lamp with a light intensity of 3KW for 3 minutes, with an irradiation intensity of 5000mj / cm 2After the irradiation, the EVA optical adhesive film is obtained. Compared with Example 4, the photoinitiator TPO and GC1005A are replaced by photoinitiator 439 in this comparative example. The absorption peak of the photoinitiator is relatively wide, with an absorption peak of 220nm-380nm in the ultraviolet region, and can absorb visible light.

[0063] Comparative Example 7

[0064] The present embodiment provides an EVA optical adhesive film, which is prepared by the following steps: by weight, 100 parts of ethylene-vinyl acetate copolymer with a VA content of 28% and a melt index of 15, 10 parts of trimethylolpropane triacrylate acrylate monomer, 0.5 parts of coupling agent vinyl triethoxysilane, 1 part of 1076 antioxidant, 0.5 parts of 770 light stabilizer, 30 parts of commercially available GTO thermal insulation slurry, 1.5 parts of photoinitiator TPO, 0.8 parts of GC1005A, and 1 part of 5400 ultraviolet absorber are mixed evenly to obtain a mixture. The mixture is mixed evenly and extruded by an extruder, and the extrusion temperature is 70°C. After extrusion, it is cooled, embossed, pulled, and rolled to obtain an uncured EVA optical adhesive film. In the present embodiment, the thickness of the uncured EVA optical adhesive film is 0.4 mm.

[0065] The uncured EVA optical adhesive film obtained in the above step was placed in a vacuum press, pre-pressed at 80°C for 4 minutes, and then irradiated under a high-pressure mercury lamp with a light intensity of 3KW for 3 minutes, with an irradiation intensity of 5000mj / cm 2 After the irradiation, the EVA optical adhesive film is obtained. Compared with Example 4, the GTO thermal insulation slurry wrapped with silica is replaced by ordinary GTO slurry in this comparative example.

[0066] Experimental example

[0067] 1. Crosslink density test

[0068] The EVA optical adhesive films provided in Examples 4-5 and Comparative Examples 1-6 were respectively laminated in the order of PET release film / EVA optical adhesive film / glass, and then pre-pressed for 4 minutes at 80°C in a vacuum press, and then irradiated for 3 minutes under a high-pressure mercury lamp with a light intensity of 3KW for curing and cross-linking. The irradiation intensity was 5000mj / cm 2 After curing and cross-linking, the release film was removed and the cross-linking density was tested by xylene extraction method. The test results are shown in Table 1:

[0069] Table 1

[0070] Serial number Crosslink density Example 4 85% Example 5 80% Comparative Example 1 72% Comparative Example 2 60% Comparative Example 3 70% Comparative Example 4 63% Comparative Example 5 65% Comparative Example 6 72%

[0071] It can be seen from the above results that the wavelength range of the ultraviolet absorber affects the cross-linking density of the final cure. The highly weather-resistant ultraviolet and infrared blocking EVA optical adhesive film provided in Examples 4-5 of the present application can obtain a higher degree of cross-linking. It can be seen that the separation of the absorption peak regions of the ultraviolet absorber and the photoinitiator is helpful for the cross-linking and curing of the optical adhesive film.

[0072] 2. UV aging resistance test

[0073] The EVA optical adhesive films provided in Examples 4-5 and Comparative Examples 1-6 were respectively used to prepare samples: two pieces of 2 mm thick glass were used to sandwich a piece of EVA optical adhesive film, and the sample size was 300 mm*300 mm. The sample was placed in a vacuum press, pre-pressed at 80°C for 4 min, and then irradiated under a high-pressure mercury lamp with a light intensity of 3 KW for 3 min to perform curing and cross-linking. The irradiation intensity was 5000 mj / cm 2 After curing and cross-linking, the UV aging resistance test was carried out. The irradiation was carried out for 1000 hours at 280nm-400nm and 120KWh / m. The yellowing was observed at regular intervals and the yellowing index was measured. The test results are shown in Table 2:

[0074] Table 2

[0075]

[0076] The above-mentioned aging test results show that poorly cured EVA film is prone to white spots under ultraviolet irradiation. The highly weather-resistant UV-infrared blocking EVA optical film provided in Examples 4-5 of the present application can absorb ultraviolet rays in the entire UV range by using a UV absorber and a photoinitiator in combination, thereby effectively preventing aging and making the EVA film have good weather resistance. At the same time, it can also effectively prevent the problem of shrinkage of the insulation material due to ultraviolet irradiation.

[0077] 3. Light transmittance test

[0078] According to the method of Experimental Example 2, the EVA films provided in Examples 4-5 and Comparative Examples 1-6 were prepared as samples. After the samples were prepared, the glass transmittance meter was used to test the visible light, ultraviolet blocking and infrared blocking of the glass. After the ultraviolet light aging test of Experimental Example 2, the glass visible light, ultraviolet blocking and infrared blocking were tested again. The changes in the values ​​before and after were compared. The test results are shown in Table 3:

[0079] Table 3

[0080]

[0081] The above-mentioned transmittance test results show that the infrared blocking rate of glass that shrinks will also decrease at the same time, and the appearance of white spots due to poor curing will affect the visible light transmittance. In Examples 4-5 of the present application, the ultraviolet absorber and the photoinitiator are compounded so that the ultraviolet rays in the entire ultraviolet range are absorbed. The infrared blocking rate and ultraviolet blocking rate of the EVA film are only slightly reduced after the aging test, while the infrared blocking rate and ultraviolet blocking rate of the EVA film in the comparative example are significantly reduced after the aging test.

[0082] 4. Aging test in air

[0083] The EVA films provided in Example 4 and Comparative Examples 5-7 were used to prepare samples according to the method provided in Test Example 2. After curing, four pieces of glass were placed in outdoor air for half a year to observe whether the appearance of the glass was shrinking. The test results are shown in Table 4:

[0084] Table 4

[0085]

[0086] By comparing the test results of Example 4 with those of Comparative Example 7, it can be seen that the thermal insulation slurry of GTO wrapped with silica can effectively prevent the shrinkage problem caused by long-term placement in the air; by comparing the test results of Example 4 with those of Comparative Examples 5 and 6, it can be seen that the ultraviolet absorber and photoinitiator used in the EVA film provided in Example 4 of the present application have a good effect in preventing shrinkage.

[0087] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A highly weather-resistant ultraviolet and infrared blocking EVA optical film, characterized in that: The optical adhesive film is prepared from the following raw materials in parts by weight:

2. The highly weather-resistant ultraviolet and infrared blocking EVA optical adhesive film according to claim 1, characterized in that: The ethylene-vinyl acetate copolymer has a melt index of 5-43 g / 10 min and a VA content of 28-33%.

3. The highly weather-resistant ultraviolet and infrared blocking EVA optical adhesive film according to claim 1, characterized in that: The acrylate monomer is at least one of trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, trimethylolpropane diacrylate, and di-trimethylolpropane tetraacrylate (ditrimethylolpropane tetraacrylate).

4. The highly weather-resistant ultraviolet and infrared blocking EVA optical adhesive film according to claim 1, characterized in that: The photoinitiator includes at least one of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide or liquid 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and at least one of GC-1005A and GC-1003.

5. The highly weather-resistant ultraviolet and infrared blocking EVA optical adhesive film according to claim 1, characterized in that: The ultraviolet absorber is one of ultraviolet absorber 5400 and ultraviolet absorber UV-971.

6. The highly weather-resistant ultraviolet and infrared blocking EVA optical adhesive film according to claim 1, characterized in that: The coupling agent is at least one of vinyl triethoxysilane, γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane, and γ-(methacryloyloxy)propyl trimethoxysilane.

7. The highly weather-resistant ultraviolet and infrared blocking EVA optical adhesive film according to claim 1, characterized in that: The antioxidant is antioxidant 1076; the light stabilizer is light stabilizer 770.

8. The highly weather-resistant ultraviolet and infrared blocking EVA optical adhesive film according to claim 1, characterized in that: The thermal insulation slurry is an oily dispersion of GTO wrapped in silica.

9. A method for preparing the highly weather-resistant ultraviolet and infrared blocking EVA optical adhesive film according to any one of claims 1 to 8, characterized in that: The steps include: S1. Prepare thermal insulation slurry, disperse GTO powder in water to obtain a dispersion; add sodium silicate aqueous solution to the dispersion, stir to react, obtain a reaction solution, adjust the pH of the reaction solution to 8-10, continue to stir to react, filter to obtain a reactant, dry the reactant and then sinter to obtain a silica-coated GTO powder, mix the silica-coated GTO powder with a dispersant and a solvent to obtain the thermal insulation slurry; S2. Prepare an EVA optical adhesive film, mix the ethylene-vinyl acetate copolymer, acrylate monomer, photoinitiator, ultraviolet absorber, coupling agent, light stabilizer, and thermal insulation slurry according to a ratio, perform pre-pressing treatment, and after the pre-pressing treatment, irradiate under a high-pressure mercury lamp to obtain the EVA optical adhesive film.

10. The preparation method according to claim 9, characterized in that: In the step S1, the concentration of the dispersion is 10-30%, the concentration of the sodium silicate aqueous solution is 1-30%, and the stirring reaction time is 1-3 hours; in the sintering process, the sintering temperature is 600-1000°C, and the sintering time is 4-6 hours; in the step S2, the pre-pressing temperature is 60-80°C, the pre-pressing time is 4-6 minutes, the irradiation time of the high-pressure mercury lamp is 2-5 minutes, and the irradiation intensity is 3000-10000mj / cm 2 ; In the step S1, the dispersant is one of BYK-ATU, DP-810, EFKA-5220, BYK-110, S-32500, BYK-161, S-2000, EFKA-4010; the solvent is one or more of cyclohexane, toluene, xylene, ethylene glycol butyl ether acetate, and propylene glycol methyl ether acetate.

Citation Information

Patent Citations

  • Core-shell anti-infrared auxiliary agent, heat-insulation EVA non-flowing glue film and preparation method

    CN104130725A

  • Infrared adjustment intelligent thermal insulation EVA film and preparation method thereof

    CN105086859A